2004
DOI: 10.1073/pnas.0402455101
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of B cell differentiation in the central nervous system of patients with multiple sclerosis

Abstract: Clonally expanded populations of B cells carrying somatic mutations of Ig variable (V) region genes have been detected in the CNS of subjects with multiple sclerosis (MS), suggesting that a process of B cell affinity maturation with ensuing production of potentially pathogenic autoantibodies may occur inside the CNS. Here, we have characterized the B cell subsets present in the cerebrospinal fluid (CSF) of MS patients and of individuals with other inflammatory neurological disorders by flow cytometry. CD19 ؉ C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
240
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(271 citation statements)
references
References 48 publications
22
240
1
4
Order By: Relevance
“…Further characterization of the IgG1 ASCs in the CSF of MS patients showed that these cells express CD38, CD138, and HLA‐DR, together with dim levels of CD19 and high levels of CD27. This is in line with the results of a previous study characterizing intrathecal B cells,15 but contrasts another study that demonstrated increased numbers of CD19 – CD138 + plasma cells 16. Importantly, we show for the first time that the intrathecal IgG1 ASCs express high levels of Ki‐67, suggesting that the cells are newly derived and proliferate intrathecally.…”
Section: Discussionsupporting
confidence: 91%
“…Further characterization of the IgG1 ASCs in the CSF of MS patients showed that these cells express CD38, CD138, and HLA‐DR, together with dim levels of CD19 and high levels of CD27. This is in line with the results of a previous study characterizing intrathecal B cells,15 but contrasts another study that demonstrated increased numbers of CD19 – CD138 + plasma cells 16. Importantly, we show for the first time that the intrathecal IgG1 ASCs express high levels of Ki‐67, suggesting that the cells are newly derived and proliferate intrathecally.…”
Section: Discussionsupporting
confidence: 91%
“…Accumulation of innate and adaptive immune cells in the choroid plexus stroma in multiple sclerosis patients is associated with the appearance of increased numbers of memory/ effector T cells (Fig. 6) [51,68], B cells, and antibodyproducing cells in the CSF of these patients [26], suggesting that immune cells that invade the ventricles have to eventually pass the choroid plexus epithelium. Indeed, mimicking the increase of CNS danger signals by intracerebroventricular injection of TNF-α, besides eliciting an inflammatory response throughout the brain, leads to T cell accumulation in the choroid plexus stroma [169].…”
Section: Neuroimmune Function Of the Choroid Plexuses In Neurologicalmentioning
confidence: 99%
“…In CNS infectious diseases, such as subacute sclerosing panencephalitis (SSPE), neurosyphilis, mumps meningitis, progressive rubella panencephalitis, cryptococcal meningitis, and varicella zoster virus vasculitis, the oligoclonal IgG is directed largely against the infectious agent that causes the disease (reviewed in reference 12). Increased CNS IgG synthesis is accompanied by an elevated number of CD19 ϩ B cells and the appearance of post-germinal center reaction plasmablast/plasma cells (4,6,18). We previously used laser capture microdissection and single-cell PCR to identify expanded clones among the CD38 ϩ B cells found within the parenchyma of SSPE brain (3).…”
Section: Infectious and Inflammatory Diseases Of The Cns Are Often Chmentioning
confidence: 99%